Prediction of coronary heart diseases using supervised machine learning algorithms - Salam, Nazia Binte; Raisa, Samiha; Rashid, Rahela Atia; Noor, Asmita; Obaed, Sin-Sumbil Binte (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.